Influence of sequential fermentations with nonSaccharomyces and Saccharomyces cerevisiae on the colour of red winemaking - Leitão, Cátia Martins (2019)
Selected strains of non-Saccharomyces can positively contribute to improve red wine colour by the production of stable pigments thanks to the differences in its metabolism. The main aim of this work was to evaluate the influence of sequential fermentations with nonSaccharomyces and S. cerevisiae at two different temperatures on red wine colour and identify the genus of four strains used on the oenological assay by molecular biology techniques. Physical-chemical parameters and anthocyanin profile were analysed on final wines. Molecular biology techniques were used to determine the yeast genus of IPSMA6, R20VL4, 21A110 and 15C6 strains. Nucleotide sequences of these strains were compared with available DNA sequences in GenBank using BLAST. Strain 21A110 and R20VL4 were identify as Hanseniaspora, strain IPSMA6 was identify as Lachancea and strain 15C6 was identify as Metschnikowia. Respecting to the oenological assay, results showed that the yeast specie/strain used in sequential fermentation has substantial influence on the formation of stable compounds. Moreover, the lower temperature during fermentation improved the anthocyanin profile. Yeast selection and its characterization is important to improve the colouring matter of wine and, consequently, wine quality.